DETERMINATION OF HYDRODYNAMIC PARAMETERS OF THE SEALED PRESSURE EXTRACTOR - Kosulina, Nataliaya; Kosulin, Stanislav; Korshunov, Kostiantyn; Nosova, Tetyana; Nosova, Yana (Informatyka, automatyka, pomiary w gospodarce i ochronie środowiska, 2021)
The subject matter of the article: Sealed extractor with pressure. The goal of the work: Determination of hydrodynamic parameters of the sealed extractor with pressure. The following tasks were solved in the article: Theoretical research on the creation of a sealed extractor with pressure. It is need to development of ways of implementation and practical recommendations for the given technical solutions in the experimental sample. The following methods are used: Mathematical modeling, differential and integral calculus, experimental research methods. The following results were obtained: The processes occurring in sealed extractors are described mathematically. Parameters that affect the performance of aggregates are determined. Conclusions: As a result of the analysis of the technological process and equipment used in the factories for primary processing of wool, shortcomings and problems are identified and means for their elimination are proposed. It is proposed to use small-sized equipment to work on waste-free technology based on a hydrodynamic pressure extractor. Extraction as an efficient mass transfer process for removing organic components from aqueous solutions has the advantages of low operating temperatures and efficiency. The design features of the sealed pressure extractor are as follows: high angular velocities, the moment of inertia of rotating details, powerful pressure, the presence of nodes that provide a supply and discharge of liquids, tightness. The kinematic and geometric parameters of the rotor affect the sealed extractors’ performance). In sealed extractors, the heavy fraction in the field of centrifugal forces will accumulate on a large radius of the inner side of the rotor and for its movement it is necessary to create an excess pressure at the extractor inlet.